Pengaruh Harga Dan Kualitas Pelayanan Terhadap Keputusan Penggunaan Jasa Wedding Organizer Ratu Rias Sitanggal - Siti Nurzanah Afiyanti; Muhammad Syaifulloh; Indah Dewi Mulyani (Jurnal Manajemen Riset Inovasi, 2023)
This study aims to determine the effect of Price and Service Quality on the Decision to Use the Services of a Wedding Organizer Ratu Rias. This type of research uses quantative. Data collection methods with direct observation, interviews or interviews, questionnaire data through google forms and data collection with documentation. The population is consumers who have used services, with a research sample of 64 respondents. The data analysis tool used is multiple linear regression using SPSS version 22. The tests of this research are Validity and Reliability Test, Classical Assumption Test such as Normality Test, Multicolonierity Test and Heteroscedasticity Test. Multiple Linear Regression Analysis Test using T Test and F Test.The results of the data analysis obtained that: 1) price has no effect and is not significant on the decision to use the services of a wedding organizer Ratu Rias Sidate. It is known that the significance value for the effect of X1 on Y is 0.215 > 0.05. And the calculated t value is 1.254 < t table is 1.670. 2) While the Quality of Service has a positive and significant influence on the decision to use the services of a wedding organizer Ratu Rias. It is known that the significance value of X2 to Y is 0.000 < 0.05. And the calculated t value is 4.903 > t table is 1.670. 3) simultaneously the Price and Quality of Service significantly and positively affect the Decision to Use Services. It is known that the significance value for the effect of price and service quality simultaneously on the decision to use services is 0.000 < 0.005 and the calculated f value is 12.629 > f table 3.15.